Nominal classification in aboriginal Australia - Harvey, Mark, 1958-; Reid, Nicholas (Studies in language companion series, 1997)
This volume aims to extend both the range of analyses and the database on nominal classification systems. Previous analyses of nominal classification systems have focussed on two areas: the semantics of the classification system and the role of the system in discourse. In many nominal classification systems, there appear to be a significant percentage of nominals with an arbitrary classification. There is a considerable body of literature aimed at elucidating the semantic bases of clasification in such systems, thereby reducing the degree of apparent arbitrariness. Contributors to this volume.